Nursing Care For Patients With Second-Degree Decubitus Wounds in The Destructive Phase Using Wound Care with Honey Against The Problem of Tissue Damage Tissue Integrity in General Ahmad Yani Hospital Metro City - Hasanah, Nur; Wardoyo, Eko (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The purpose of this study was to determine the effectiveness of destructive phase II decubitus wound care using honey at Jendral Ahmad Yani Metro Hospital. Method: The method in this scientific work is a descriptive approach to nursing care involving 2 decubitus patients, the instruments used are assessment sheets, head to toe¸ and wound observation sheets, the application of wound care using honey is carried out for 4 days in patient 1 and 5 days in patient 2, with the intensity of giving honey once a day every day. Result: The results of this study found that the main problem that arose in both patients was damage to tissue integrity, the intervention was arranged by performing wound care using pure honey, the implementation was carried out for 4 days and 5 days in each patient, the wound nursing evaluation began to improve on day 3 of wound care using honey. Conclusion: The recommendation that the author can give is that honey can cure and accelerate wound healing, so it can be applied to other types of wounds not only decubitus wounds.